Penerapan Teknologi Tepat Guna bagi Masyarakat Desa Cikerai Menggunakan Barang Sederhana untuk Mengecek Kadar Kesuburan Tanah - Rendi Hamat Yani; Surachman Surachman; Reza Sundari; Muhammad Nabil Istiantoro; Chaerus Salam (Universitas Maritim AMNI Semarang, 2024)
Soil is a nutrient for plants and they grow well and optimally. The nutrients needed by plants include macro elements and micro elements. So that plants can grow well. For this reason, we need a tool to check soil fertility levels from makeshift materials or simple items. The aim of Community Service (PKM) in the field of appropriate technology by KKM group 40 in Cikerai Village is to implement measuring soil fertility levels from simple items. The PKM method used is approach, direct introduction, and knowledge of soil fertility measuring tools. The results of this PKM were responded well by farmers in the Cikerai Village area even though at first they seemed confused, so this tool can be used in the future.